Playfulness and childhood: weavings of thought - Suárez Vaca, María Teresa; Universidad Pedagógica y Tecnológica de Colombia; Salamanca Manrique, Zoraida; Universidad Pedagógica y Tecnológica de Colombia; Morales Mora, Lola María; Pulido Cortés, Óscar; Universidad Pedagógica y Tecnológica de Colombia; Duarte Báez, Leidy Yulieth; Universidad Pedagógica y Tecnológica de Colombia; Chacón Quiroga, Karen Julieth; Universidad Pedagógica y Tecnológica de Colombia; Ojeda Suárez, Manuel Alejandro; Universidad Pedagógica y Tecnológica de Colombia; Albarracín Camacho, Leidy Yohanna; Acosta Gutiérrez, Joselín; Romero Alfonso, Sonia Lucía; Universidad Pedagógica y Tecnológica de Colombia; Lara Buitrago, Paola Andrea; Universidad Pedagógica y Tecnológica de Colombia; Bohórquez Olaya, Claudia Inés; et al. (UPTC Editorial, 2023)
Ludic and childhood: weavings of thoughts... is a book that presents conceptual aspects that compose and characterize playfulness from philosophical perspectives. It clarifies and proposes a particular and innovative way of understanding playfulness as a structural dimension of the human being and as a state of the subjects themselves. Playfulness is approached, allowing conditions of exploration, reflection and sensibility to emerge, it becomes an enigma that captivates to wonder and think about it in philosophical tones as a state and experience; a way of being and being that urges vital sensations of wellbeing and creation. This writing proposal affirms playfulness from different points of view and components. It distances itself from the mechanization of actions and refuses to be conceived as an instrumentalized recipe. One of the bets is to stress the relationship between play and playfulness and to contemplate aspects that function as lines of flight and thought, a network of voices that converse, where play is a genuine expression. The journey of words and meanings problematizes some questions such as: What is philosophical in playfulness? What is playful in philosophy? Is playfulness a state of infancy? What are the philosophical paths that think playfulness? The chapters are constructed from conceptual inquiries and relationships. They are a weaving of thoughts that works as a web of meanings and perspectives, they unfold as ways to think and feel, the authors wrote from the movement of their questions and interests, in order to communicate what they have investigated and open new possibilities and concerns. This book, as an object of thought, goes through different fields related to playfulness: friendship, dreams, happiness, leisure, heterotopias, sensibility, creation, body, pedagogy, play and voices of childhood.